Childhood Obesity in Florida: A Narrative Review on Current Trends and Interventions - Corey Parliament; E. McKenzie Driscoll; Kristin Samuels; Laura Ward; Tammy M. Baranowski; Tara Kessinger; Alireza Jahan-mihan (University of North Florida, 2016)
We examine current research on childhood obesity (CO) trends and intervention strategies in Florida. The fiscal, emotional, and health-related costs related to general obesity are staggering. Unfortunately, CO-related publicity, research, policy, and interventions have not been entirely successful in addressing the problem. Florida ranks 35th nationally in prevalence of CO. Data from the Centers for Disease Control and Prevention (CDC) 2013 report a statistically significant decrease in Florida's rate of CO among 2-4 year-olds participating in Florida's Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) from 2008-2011. Whereas Florida still has significant room for improvement on the issue of CO, its relatively low CO prevalence indicates a step in the right direction. Information provided herein provides valuable insight, resource information, and motivation to healthcare providers, particularly registered dietitian nutritionists (RDNs). As nutrition experts employed in various areas of society, RDNs are advantageously situated to contribute significantly to the CO solution. Florida appears to benefit from interdisciplinary collaborations among healthcare facilities, schools, faith-based organizations, governmental agencies, and grassroots programs that may play a major role in the current fight against CO.